Maritime Patrol Collaboration with Indonesian Maritime Law Enforcement Agencies - Haidul Firman Sitorus; Budiman Djoko Said; Panji Suwarno; Pujo Widodo; Herlina Juni Risma Saragih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
With so many agencies patrolling separately, the patrol becomes ineffective and inefficient. Each agency needs a budget and conducts repeated ship inspections. The expected condition is when all agencies can collaborate in carrying out patrols. Researchers used qualitative methods with exploratory designs. Interviews were conducted with informants from Bakamla, TNI AL, Polair, Bea Cukai, PSDKP, and KPLP. The results of the research show that collaboration is needed to combine various elements of patrols from various authorities in the sea. Researchers suggest collaboration between agencies with joint base assets and create a ship inspection information system in real-time.